Cognitive function of young male tennis players and non-athletes - Pacesová, P.; Šmela, P.; Kracek, S.; Kukurová, K.; Plevková, L. (Acta Gymnica, 2018)
Background: Cognitive functions can be defined as the ability of individuals to participate, recognize and plan responses to external and internal impulses. We can define attention as the active focus of our consciousness and the ability to concentrate mental functions on a certain activity. In competitive tennis, attention, especially conscious attention which is controlled by cognitive and volitional processes plays a significant role.